2022
DOI: 10.3389/fmolb.2022.1081166
|View full text |Cite
|
Sign up to set email alerts
|

Functions and evolution of FAM111 serine proteases

Abstract: Proteolysis plays fundamental and regulatory roles in diverse cellular processes. The serine protease FAM111A (FAM111 trypsin-like peptidase A) emerged recently as a protease involved in two seemingly distinct processes: DNA replication and antiviral defense. FAM111A localizes to nascent DNA and plays a role at the DNA replication fork. At the fork, FAM111A is hypothesized to promote DNA replication at DNA-protein crosslinks (DPCs) and protein obstacles. On the other hand, FAM111A has also been identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 81 publications
1
29
0
Order By: Relevance
“…Although several m 6 A modification sites were also predicted in FAM111A transcript, m 6 A modification did not post‐transcriptionally regulate FAM111A transcript stability. FAM111A is a single‐stranded DNA‐binding serine protease, which promotes DNA synthesis 53 . FAM111A was also reported as a replication factor needed for PCNA loading during DNA replication 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Although several m 6 A modification sites were also predicted in FAM111A transcript, m 6 A modification did not post‐transcriptionally regulate FAM111A transcript stability. FAM111A is a single‐stranded DNA‐binding serine protease, which promotes DNA synthesis 53 . FAM111A was also reported as a replication factor needed for PCNA loading during DNA replication 46 .…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 Accumulating evidence in recent years has shown that FAM111B mutation is associated with increased susceptibility to malignancy. 7 , 32 Overexpression of FAM111B in cancer cells has been associated with accelerated cancer progression and poor clinical outcomes. 8 , 9 It is still unknown if FAM111B can regulate the development of various malignancies through known or unidentified molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transient transfection of FAM111A in human cells exhibited a strong inhibitory effect on viral DNA replication, viral protein expression, and virus replication, further confirming the antiviral function of FAM111A for SPI-1-lacking VACV. The trypsin-like domain of FAM111A contains a catalytic triad including His385, Aps439, and Ser541 24,25 and a DNA-binding domain that plays essential (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transient transfection of FAM111A in human cells exhibited a strong inhibitory effect on viral DNA replication, viral protein expression, and virus replication, further confirming the antiviral function of FAM111A for SPI-1-lacking VACV. The trypsin-like domain of FAM111A contains a catalytic triad including His385, Aps439, and Ser541 24,25 and a DNA-binding domain that plays essential roles for its localization at the replication forks 5,23 . FAM111A was also shown to bind to the large T antigen of SV40 and inhibit the formation of the replication center of SV40 mutants, demonstrating its broad antiviral activity for DNA viruses 7 .…”
Section: Discussionmentioning
confidence: 99%